Potential of Fungi Isolate as a Biological Control of White Root Disease (Rigidoporus sp.) on Rubber Plant - Mariana Mariana; Kurnia Utami Dewi; Samharinto Samharinto; Ismed Setya Budi (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2020)
Rigidoporus Sp. is a white root fungus which is the main diseases problems on rubber plants in the wet and dry lands of South Kalimantan. An economically and ecologically beneficial control solution for this problem soil contagion was by using antagonistic fungi. This research was aimed to study the potential of rhizosphere and endophytic fungi in swampland, to control white root fungus on rubber plants. The research used exploratory method. Rhizospheric fungi were explored from swamp rubber plant roots at Pulau Damar village Hulu Sungai Utara District; endophytic fungi were isolated from leaves and jelutung swamps (Dyera lowii) which is rubber-like plants. The isolates found then were screened based on the percentage of inhibition using the dual culture method between pathogens and test isolates, also observed the interaction mechanism and viability test. The research in the laboratory was arranged using a Completely Randomized Design with one factor i.e. the type of antagonistic fungi. Five isolates which had the highest inhibitory power were isolates I13K4R, I7K3R, I1K2R, I6K2R, and I1E with successive inhibitions 95.00%, 83.00%, 76.50%, 62.50% and 53.00%. Thus, isolates have included potential antagonistic agents because they had the ability in space competition more than 50% and proven to be able to paralyze Rigidoporus. The viability test results showed that the isolate that had germination capability of more than 60% were respectively I13K4R 88.05%, I7K3R 87.33%, I1K2R 86.93%, I6K2R 72.85%, and I1E 74.78%.